Refining concepts for empirical multimodal research: defining semiotic modes and semiotic resources - Castaldi, Jacopo (Frontiers in Communication, 2024)
The issue of defining key concepts in multimodal research is at the same time ongoing and of pivotal importance. Building on John Bateman's categorisation of modes, and paying special attention to the concept of materiality within the discussion, the paper provides a clear differentiation between semiotic modes and semiotic resources and discusses the relationship between the two. These will be defined by also looking at how they differ from another key concept in multimodal research, i.e. media, and examples will be provided to illustrate how the newly defined concepts can guide empirical investigations of multimodal texts and their reception. The paper aims to continue the discussions around these key concepts amongst multimodal scholars, so that agreement in the field can eventually be reached. the last part of his assertion, I believe it may be equally difficult to establish what different things modes are good at if we do not first establish what they are.A similar point can be made for the concept of semiotic resources, which is sometimes seen as an overall umbrella term for anything that can be used for meaning-making, and whose nature and composition is often vaguely defined. Indeed, as Bateman (2021a, p. 56) states:Considerable theoretical uncertainty therefore remains concerning just how potentially 'overlapping' semiotic systems might best be approached, both theoretically and practically during analysis. This is not helped by the fact that the notion of 'semiotic resource' is also intrinsically vagueanything that may serve a semiotic purpose may be a resource: van Leeuwen even writes, for example, of 'genre' being a semiotic resource (van Leeuwen 2005: 128). This does not provide support for empirical analysis.